2013
DOI: 10.1007/s00421-013-2608-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in the involution of the different neural loops with age

Abstract: The purpose of the study was to compare the effects of sensory manipulations on postural control for subjects of different ages. A young group of subjects (n = 17; 20.0 ± 1.3 years) and an old group of subjects (n = 17; 74.7 ± 6.3 years) were compared in 14 postural conditions [2 reference conditions and 12 sensory manipulation conditions: eyes closed, cervical collar, tendon vibration, electromyostimulation, galvanic vestibular stimulation (2 designs), foam surface] on a force platform. Spatio-temporal parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…These adaptive neural mechanisms render older individuals more sensitive to electrical vestibular stimuli than younger individuals (Peters et al, 2016). Previous studies (Deshpande and Patla, 2007; Maitre et al, 2013a) have indicated greater effects of GVS on the postural control of older individuals than on that of younger individuals. Unlike other studies involving young participants (Balter et al, 2004b; Yang et al, 2015; Maitre and Paillard, 2016), the greater effect of GVS on older individuals could have reduced the difference between the active and non-active older groups in the present study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These adaptive neural mechanisms render older individuals more sensitive to electrical vestibular stimuli than younger individuals (Peters et al, 2016). Previous studies (Deshpande and Patla, 2007; Maitre et al, 2013a) have indicated greater effects of GVS on the postural control of older individuals than on that of younger individuals. Unlike other studies involving young participants (Balter et al, 2004b; Yang et al, 2015; Maitre and Paillard, 2016), the greater effect of GVS on older individuals could have reduced the difference between the active and non-active older groups in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, to some extent, physical activity performed on a regular basis may be able to protect the postural system from aging effects. To understand how aging and physical activity affect postural control, external perturbation techniques, more precisely sensory manipulation techniques (i.e., mechanical, electrical, chemical, optical) have been widely used (Gauchard et al, 2001, 2003; Hue et al, 2004; Jeka et al, 2006; Deshpande and Patla, 2007; Maitre et al, 2013a,b, 2015; Eikema et al, 2014; Maitre and Paillard, 2016). The main objective of these techniques was to alter or manipulate sensory information (i.e., afferents emanating from the visual, vestibular and somatosensory systems) in order to analyze postural compensatory strategies, and to understand how individuals cope so that they can reorganize their posture in a challenging sensory context.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be because the studies that used muscle vibration had small participant numbers, and /or the response to muscle vibration is more complicated to interpret as it reflects the peripheral function, the weighting applied by CNS to the proprioceptive information during a functional task, and the capacity of the postural muscles to respond. When comparing the postural response to vibration between young and elderly individuals, some studies observed no difference (Abrahámová et al, 2009;Brumagne et al, 2004), a lower response (Hay et al, 1996;Pyykko et al, 1990;Quoniam et al, 1995), or a greater response in postural sway (Maitre et al, 2013) in elderly than young.…”
Section: Age-related Changes In the Sensory Systemmentioning
confidence: 99%